Effectiveness of oseltamivir on disease progression and viral RNA shedding in patients with mild pandemic 2009 influenza A H1N1: Opportunistic retrospective study of medical charts in China - Yu, H; Liao, Q; Yuan, Y; Zhou, L; Xiang, N; Huai, Y; Guo, X; Zheng, Y; Van Doorn, H; Farrar, J; Gao, Z; Feng, Z; et al. (2010)
Objective: To describe the clinical features and effectiveness of oseltamivir on disease progression and viral RNA shedding in patients with mild pandemic 2009 influenza A(H1N1) virus infection. Design: Opportunistic retrospective review of medical charts of patients with confirmed 2009 H1N1 identified through the national surveillance system in China from May to July 2009. Setting: Under coordination of the Ministry of Health, local health departments were asked to collect medical records of confirmed patients and send them to the Chinese Centre for Disease Control and Prevention on a voluntary basis as part of the public health response. Population: 1291 patients with confirmed 2009 H1N1 infection and available data for chart review. Main outcome measures: Demographic characteristics, comorbidities, symptoms and signs, laboratory tests, findings on chest radiography, antiviral treatment, duration of fever, and duration of viral RNA shedding. Results: The median age of 1291 patients was 20 years (interquartile range 12-26); 701 (54%) were male. The most common symptoms were fever (820, 64%), cough (864, 67%), sore throat (425, 33%), sputum (239, 19%), and rhinorrhoea (228, 18%). Of 920 patients who underwent chest radiography, 110 (12%) had abnormal findings consistent with pneumonia. Some 983 (76%) patients were treated with oseltamivir from a median of the third day of symptoms (2-4). No patients required admission to the intensive care unit or mechanical ventilation. 2009 H1N1 was shed from one day before onset of symptoms to up to eight days after onset in most (91%) patients, with a median of 5 (3-6) days of shedding after onset. Treatment with oseltamivir significantly protected against subsequent development of radiographically confirmed pneumonia (odds ratio 0.12, 95% confidence interval 0.08 to 0.18), and treatment started within two days of symptom onset reduced the duration of fever and viral RNA shedding. Conclusions: Chinese patients with 2009 H1N1 infection predominantly presented with features of uncomplicated, self limiting acute respiratory illness. 2009 H1N1 might be shed longer than seasonal influenza virus. Treatment with oseltamivir was associated with a significantly reduced development of radiographically confirmed pneumonia and a shorter duration of fever and viral RNA shedding. Though these patients benefited from treatment, the findings should be interpreted with caution as the study was retrospective and not all patients underwent chest radiography.